CONFLICT BETWEEN THE HUSBAN AND WIFE IN THE IRAQI CONTEMPORARY FAMILY . - حسين حطيم عطية, علي (Al-Adab Journal, 2018)
The conflict between the husband and the wife in the contemporary Iraqi families has been considered a basic one as having huge effects on the families . There are special cases between the husband and the wife that lead to this kind of struggle for long periods without being resolved and consequently affecting on all sides of the family. This resulted into having the family liver under a very difficult condition and become living in unsettled state owing to this kind of struggle. This matter requires quick resolution and hastily be resolved because it is unresolved , then it will lead to increasing tensions between the husband and the wife.The research includes the following:Introduction : It includes summary of the struggle between the husband and the wife along with showing reasons behind hat .It includes problem and importance of the research.Concepts mentioned in the present paper:-.-Struggle. - marriage happiness. – Personality.Reasons of struggle between the husband and the wifeTo what extent the husband and the wife understand their duties.The effect of the struggle on their sonsThe factors helping to reduce tension in struggle between the husband and the wife.Result and recommendations